Chinese newborn screening for the incidence of G6PD deficiency and variant of G6PD gene from 2013 to 2017. Issue 1 (23rd September 2019) - Liu, Zhidai; Yu, Chaowen; Li, Qingge; Cai, Ren; Qu, Yiping; Wang, Weipeng; Wang, Jie; Feng, Jinwen; Zhu, Wenbin; Ou, Mingcai; Huang, Weitong; Tang, Deguo; et al.
Abstract: Glucose‐6‐phosphate dehydrogenase (G6PD) deficiency is one of the most common X‐linked enzymopathies caused by G6PD gene variant. We aimed to provide the characteristics of G6PD deficiency and G6PD gene variant distribution in a large Chinese newborn screening population. We investigated the prevalence of G6PD in China from 2013 to 2017. Then, we examined G6PD activity and G6PD gene in representative Chinese birth cohort to explore the distribution of G6PD gene variant in 2016. We then performed multicolor melting curve analysis to classify G6PD gene variants in 10, 357 neonates with activity‐confirmed G6PD deficiency, and DNA Sanger sequencing for G6PD coding exons if hot site variants were not found. The screened population, organizations, and provinces of G6PD deficiency were increased from 2013 to 2017 in China. The top five frequency of G6PD gene variants were c.1376G>T, c.1388G>A, c.95A>G, c.1024C>T, and c.871G>A and varied in different provinces, with regional and ethnic features, and four pathogenic variant sites (c.152C>T, c.290A>T, c.697G>C, and c.1285A>G) were first reported. G6PD deficiency mainly occurs in South China, and the frequency of G6PD gene variant varies in different regions and ethnicities.